The Cauchy Problem for a Dissipative Periodic 2-Component Degasperis-Procesi System. (22nd July 2014) - Ming, Sen; Yang, Han; Yong, Ls
Abstract : The dissipative periodic 2-component Degasperis-Procesi system is investigated. A local well-posedness for the system in Besov space is established by using the Littlewood-Paley theory and a priori estimates for the solutions of transport equation. The wave-breaking criterions for strong solutions to the system with certain initial data are derived.